BgTEP: An Antiprotease Involved in Innate Immune Sensing in Biomphalaria glabrata - Portet, Anaïs; Galinier, Richard; Pinaud, Silvain; Portela, Julien; Nowacki, Fanny; Gourbal, Benjamin; Duval, David (Frontiers in Immunology, 2018)
Insect Thioester-containing protein (iTEP) is the most recently defined group among the TEP superfamily. TEPs are key components of the immune system, and iTEPs from flies and mosquitoes were shown to be major immune weapons. Initially characterised from insects, TEP genes homologous to iTEP were further described from several other invertebrates including arthropods, cniderians and mollusks albeit with few functional characterisations. In the freshwater snail Biomphalaria glabrata, a vector of the schistosomiasis disease, the presence of a TEP protein (BgTEP) was previously described in a well-defined immune complex involving snail lectins (FREP) and schistosome parasite mucins (SmPoMuc). To investigate the potential role of BgTEP in the immune response of the snail, we first characterised its genomic organisation and its predicted protein structure. A phylogenetic analysis clustered BgTEP in a well-conserved subgroup of mollusk TEP. We then investigated the BgTEP expression profile in different snail tissues, and followed immune challenges using different kinds of intruders during infection kinetics. Results revealed that BgTEP is particularly expressed in hemocytes, the immune-specialised cells in invertebrates, and is secreted into the hemolymph. Transcriptomic results further evidenced an intruder-dependent differential expression pattern of BgTEP whilst interactome experiments showed that BgTEP is capable of binding to the surface of different microbes and parasite either in its full length form or in processed forms. An immunolocalisation approach during snail infection by the Schistosoma mansoni parasite revealed that BgTEP is solely expressed by a subtype of hemocytes, the blast-like cells. This hemocyte subtype is present in the hemocytic capsule surrounding the parasite, suggesting a potential role in the parasite clearance by encapsulation. Through this work, we report the first characterisation of a snail TEP. Our study also reveals that BgTEP may display an unexpected functional dual-role. In addition to its previously characterised anti-protease activity, we demonstrate that BgTEP can bind to the intruder surface membrane, which supports a likely opsonin role.